Decay modes of the 9/2- isomeric state in 183Tl - Venhart, Martin; Andreyev, A. N.; Cubiss, J. G.; Wood, J. L.; Barzakh, A. E.; Van Beveren, C.; Cocolios, T. E.; de Groote, R. P.; Fedorov, D. V.; Fedosseev, V. N.; Ferrer, R.; Fink, Daniel; et al. (Physical review, 2022)
The internal transition decay and α decay of the T1/2=53.3ms, 9/2− isomeric state in the neutron-deficient isotope, 183Tl, have been studied using the Resonance Ionization Laser Ion Source and the Windmill detection setup at the ISOLDE facility at CERN. Clean samples of 183mTl were produced by selective laser ionization and subsequent mass separation. An internal transition cascade of 356.5-272.2 keV γ rays has been identified. Multipolarities of these transitions have been determined by means of simultaneous γ-ray and conversion-electron spectroscopy. Improved data for the fine structure of the 183mTl→179Au decay were deduced. This involves a 6058 keV α-decay transition, which populates a previously unknown state in 179Au, that is tentatively assigned as a (9/2−). It is interpreted as a coupling of the 1h9/2 proton-intruder with the excited 0+ state in the 178Pt core.
Im Text ist "-" und "183" hochgestellt
Gesehen am 01.06.2022